Efforts to Improve Understanding of Science Concepts Through Audio-Visual Media for Elementary School Students - Umi Istinganah (Universitas Sebelas Maret, 2020)
The purpose of this research is to improve understanding of the concept of Natural Science (IPA) in the material of the Food Digestive System in Humans. This research is a classroom action research (PTK) which is conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 17 students of class V SD Negeri Kedungmulyo for the 2020/2021 academic year. Data collection techniques using test and non-test techniques. The assessment instrument uses item items and observations of the scoring rubric. Analysis of the data used in the study included a comparative descriptive technique, namely a statistical technique by comparing the scores between cycles, the mean, the minimum score, the maximum, and the percentage. The results of the study that the use of audio-visual media can improve student learning outcomes in science subject content on the food digestive system material. The conclusion of this study is that using audio visual media can improve understanding of the concept of science in the material of the digestive system in humans in fifth grade students of SD Negeri Kedungmulyo.